Soybean yield variability and predictability from applied phosphorus sources and rhizobia inoculation in Northern Nigeria - Kabiru, Muhammad Rabiu; Buernor, Alfred Balenor; Dahhani, Sara; Hafidi, Mohamed; Jibrin, Jibrin Mohammed; Jemo, Martin (Frontiers in Sustainable Food Systems, 2024)
Supplementing soybean plants with phosphorus (P) and inoculation with effective rhizobia (Rh) strains enhance grain yield and profits and promotes sustainable agricultural practices in Nigeria. Limited field data exists on the effects of P forms (e.g., less soluble rock-P) on yield improvement with Rh or alone. We conducted a study where we grew soybeans in two agroecological zones (AEZs), i.e., Sudan (SS) and the Northern Guinea Savanna (NGS) of Nigeria. The P-treatments included no phosphorus (no-P), half the recommended amount of less soluble rock phosphate (RP), plus half the amount of water-soluble triple super phosphate (TSP). Soybean plants were subjected to one of the three different strains of Bradyrhizobia: Bradyrhizobium elkanii (Be), B. japonicum (Bj), or B. diazoefficiens strain (Bd). Control and nitrogen (40 kg N ha−1) treatments were included. The number of nodules, dry weights (DW), and shoot biomass weight were measured at flowering. A linear mixed model predicted grain yield and nodules DW variables from the managed and environmental factors, including manganese (Mn), magnesium (Mg), and the two AEZs. Soybean yield for ½RP + ½TSP gave a 27.4% relative increase to the control. Plants inoculated with the Be strain displayed the highest grain yield under the NGS soils. The linear mixed regression explained the yield and nodule variation with a trained root means square value of 0.87 and 0.82, respectively. The P sources, Rh inoculation, and the inoculated strains explained the yield variation well. Additionally, the soil-Mn content negatively impacted the yield, while the increasing soil-Mg enhanced nodule dry weight. Studies on the required Mn availability and forms in soil and the threshold concentrations of Mg for optimal N2 fixation and yield of soybeans are discussed.